The impact of a low FODMAP diet on the reduction of irritable bowel syndrome symptoms and changes in intestinal microbiota in patients – a review of current research - Idzik, Maja (Lekarz POZ, 2020)
Irritable bowel syndrome is invariably a mystery to modern medicine. Gastrointestinal symptoms occurring in IBS significantly reduce the well-being and quality of life of patients. It is estimated that many factors take part in the aetiology of disease development, including visceral hypersensitivity, disorders along the brain-intestinal axis, or chronic stress. It has been proven that a combination of pharmacotherapy, individual dietary recommendations, and often also psychotherapy can contribute to the reduction of persistent symptoms of irritable bowel syndrome. In recent years, the low FODMAP diet in patients suffering from IBS has caught the attention of the medical community. Many clinical studies and extensive meta-analyses indicate the effectiveness of the above diet in reducing abdominal pain and flatulence in patients, due to the limitation or exclusion from the diet of products rich in easily fermentable carbohydrates. These carbohydrates are less well absorbed in the human intestine, which is why they contribute to excessive gas production and the formation of flatulence. Mention is also made of the effect of the low-FODMAP diet on the change of intestinal microbiota (especially in terms of genre Bifidobacterium having a beneficial effect on bowel function) in people with irritable bowel syndrome. However, it should be remembered that the implementation of this diet is a big challenge for patients, which is why they should be under the constant care of a dietitian.